Middle Cerebral Artery Stenosis Associated with Moyamoya Pattern Collateralization - Edgell, Randall; Boulos, Alan S.; Borhani Haghighi, Afshin; Bernardini, Gary L.; Yavagal, Dileep (Frontiers in Neurology, 2010)
Background and Purpose: Moyamoya disease is a well described phenomenon presenting with terminal internal carotid artery occlusion and rete pattern of collateralization around the occlusion. The development of moyamoya-like collaterals secondary to isolated middle cerebral artery stenosis or occlusion and the natural history of this entity in Caucasians have not been well described. Methods: Cerebral angiograms and CT angiograms performed between August 2004 and August of 2006 demonstrating moyamoya collateralization at a single US center were retrospectively reviewed. All cases of middle cerebral artery stenosis associated with a rete pattern of collateralization were included in this series. Demographic, clinical, and angiographic data were obtained. Results: There were 3 cases of middle cerebral artery stenosis associated with a moyamoya pattern of collateralization. The average age of the patients was 36 years old, 2 were male, and all were Caucasian. All patients presented with ischemic symptoms. The average degree of stenosis was 91%. No stenosis was seen in the supraclinoid internal carotid arteries or elsewhere in the intracranial vasculature. Conclusion: We describe a moyamoya-like pattern of anastomosis associated with isolated severe middle cerebral artery stenosis or occlusion in Caucasians.